Media Gambar Seri dan Penguasaan Kosakata dalam Menulis Narasi Peserta Didik Sekolah Dasar - Muhimmatur Rosidah; Karsono Karsono (Universitas Sebelas Maret, 2026)
Learning narrative writing in elementary schools requires students to develop ideas coherently and choose the right words, so it requires the support of appropriate learning media. This study aims to analyze differences in narrative writing abilities based on the use of picture series media and text-based media, the level of vocabulary mastery, and the interaction between the two variables. The study used a quantitative approach with a quasi-experimental method through a 2x2 factorial design. The subjects were fourth-grade elementary school students. Data were collected through narrative writing ability tests and vocabulary mastery tests that have been declared valid and reliable, then analyzed using two-way analysis of variance. The results of the study showed differences in narrative writing abilities between students taught using picture series media and text-based media, as well as between students with high and low levels of vocabulary mastery. In addition, there was an interaction between learning media and vocabulary mastery in relation to narrative writing abilities. These findings demonstrate the importance of selecting appropriate learning media and strengthening vocabulary mastery in narrative writing learning in elementary schools.